Green Fabrication and Release Mechanisms of pH-Sensitive Chitosan–Ibuprofen Aerogels for Controlled Transdermal Delivery of Ibuprofen - Li, Chen; Wang, Ke; Xie, Dong (Frontiers in Chemistry, 2021)
Ibuprofen is a potent non-steroidal anti-inflammatory drug due to its analgesic, antipyretic and anti-inflammatory actions. However, its poor solubility in water makes it difficult to manufacture ibuprofen tablets, which limited the application of ibuprofen in drug delivery system. Polymer–drug aerogels has attracted huge interest in optimizing drug delivery efficiency and improving the physicochemical characteristics and therapeutic quality. Here, chitosan-ibuprofen aerogels with excellent swelling, high biocompatibility and better drug delivery efficiency was synthesized by a simple method. Our study found that the chitosan-ibuprofen aerogels exhibited remarkably improved thermal stability, excellent swelling ratio and high drug loading. As a consequence of these favorable properties, the chitosan-ibuprofen aerogels exhibited improved drug delivery efficiency and achieved drug prolonged administration. Our study highlights the great potential of polymer–drug aerogels in improving the drug delivery efficiency of transdermal drug delivery system.